Establishing Standardization of Plastics in Developing Countries - Maruta, Koei.; United Nations Industrial Development Organization (New York: United Nations, 1969)
This publication is the fifth of a series of monographs in the Petrochemical Industry Series to be published by the United Nations Industrial Development Organization (UNIDO). This series is designed to assist the developing countries in dealing with technical and economic problems related to the establishment and development of facilities for the manufacture of petrochemicals and consumer products. It is also concerned with basic and intermediate petrochemicals and end products, such as plastics, synthetic rubbers and synthetic fibres.
At head of title: United Nations Industrial Development Organization, Vienna.
"United Nations publication sales no. E.69.II.B.27"--T.p. verso.
"ID/SER.J/5"--T.p. verso.
Includes bibliographical references.
ne 06/03/2018
Loan
Keywords: Plastics